Peningkatan Kesadaran Hukum Tentang Konservasi Lingkungan Bagi Masyarakat Watutela - Agus Lanini; Ikhsan Syafiuddin (Universitas Lancang Kuning, 2020)
Watutela group of farmers and ranchers, who are very vulnerable to various problems of forest destruction. Lack of public understanding of the prohibition of illegal logging of forest trees in forest areas (Grand Forest Park). Seeing this situation, the increase in legal awareness, especially understanding of the legal obligations to conserve forests with the status of a grand forest park area. The method of implementing the activity begins with field observations, then makes contact with the head of the RW for administrative purposes, determining the time for activities and invitations to prospective participants in focus group discussions. The participatory discussion method was carried out in the afternoon. It can be said that the level of understanding of the community in the sense of complying with the provisions of forest conservation is still low, after the activity appears perceptions and attitudes that are in line with the provisions of conservation so that a commitment is built to maintain the sustainability of the forest while still benefiting (symbiosis mutualism).